(untitled) (Journal of Pakistan Orthopaedic Association, 2018)
Objectives: To evaluate the outcome of open tibial diaphyseal fracture managed by intra medullary inter locking nail in terms of frequency of union, range of knee motion and absence of infection. Study Design: Descriptive case series Place and duration of study: Department of Orthopedics, Jinnah Post Graduate Medical Centre, Karachi from June 2009 to December 2009 Patients and Methods: Patients with open tibial diaphysial fracture Gustilo-Anderson I-III A type managed by intramedullary static inter locking nail were included while patients with co morbids, previous knee or ankle disease with restricted movement and Gustilo-Anderson type III B-C were excluded. Patients were evaluated clinically and radiologically for union of fracture, infection and knee range of motion on monthly interval for 6 months and documented on proforma. SPSS-15.0 was used for statistical analysis. Results: 92 patients aged 18 â€“ 60 years were selected. 71 (77.2%) were males and 21 (22.8%) females. Mean age was 31.96 Â± 8.86. Gustilo-Anderson type I fracture was found in 77 (83.7%) patients, type II fracture in 11 (12%) and type III-A in 4 (4.3%) patients. Sixty-one (66.3%) patients treated within 6 hours of injury while 31 (33.7%) patients treated between 6 - 12 hours. Superficial infection was found in 11(12%) patients during initial follow up. 30 patients needed dynamization 6th week visit. On last follow up at 6 months, 3 (3.3%) patients had deep infection and 89 (96.7%) remained infection free. Three (3.3%) patients had non-union. Majority (96.7%) had range of motion 0 to 1350. Overall outcome of the patients showed 90.2% success and 9.7% failure. Conclusion: Intramedullary static Interlocking Nail is the treatment of choice in open tibial diaphyseal Gustilo-Anderson Type I-III A fractures, as it provides early mobilization of the patient, decreases hospital stay, prevents complications, improving functional outcome, thus total cost of treatment is reduced.